Feature level intentions based product recommendations with case-based reasoning - Teja Santosh, D; Ravi Kumar, KC; Chiranjeevi, P (International Journal of Computer Sciences and Engineering, 2025)
Crucial data like product features and opinions are mined from online reviews. The obtained opinions are further analyzed for orientations. These orientations that are positive, negative or neutral are counted to determine the sentiment of the feature. The product recommendations performed by using the sentiments lead to a problem called “customer churn”. This is due to the tide of sentiment change. The reviewer intention on the product feature is important in finalizing the recommended list of product cases. In order to carry out this, the statistical intentions are calculated. The product cases are generated for a product by using these calculated intentions. The statistical intentions of the common features are stabilized to uncover the finalized features at the time of product similarity calculation. This “intent-to-opine” way of product recommendations addresses the problem of customer churn in the long run.